2021
DOI: 10.1186/s13068-021-02040-7
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of ligninolysis mechanism of a newly isolated white-rot basidiomycete Trametes hirsuta X-13

Abstract: Background Lignin is a complex aromatic heteropolymer comprising 15–30% dry weight of the lignocellulose. The complex structural characteristic of lignin renders it difficult for value-added utilization. Exploring efficient lignin-degrading microorganisms and investigating their lignin-degradation mechanisms would be beneficial for promoting lignin valorization. In this study, a newly isolated white-rot basidiomycete, Trametes hirsuta X-13, with capacity to utilize alkaline lignin as the sole s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The signal in δ C /δ H 50-120/2.6-5.5 shows the information of C-H correlation from aliphatic and that in δ C /δ H 100-150/5.5-8.0 shows the information of C-H correlation from aromatic. The main structures in lignin were shown in Figure 5 , and the details of assignment were shown in Table 3 ( Ralph et al, 1994 , 1999 , 2004 ; del Río et al, 2008 , 2011 , 2012 ; Kim et al, 2008 ; Martínez et al, 2008 ; Rencoret et al, 2008 , 2009 ; Ralph and Landucci, 2010 ; Ma et al, 2021 ). The strong signals in aliphatic area were generated by β-O-4 linkage in substructures of (A) including A β (G), A β (H), A β (S), and A β (T).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal in δ C /δ H 50-120/2.6-5.5 shows the information of C-H correlation from aliphatic and that in δ C /δ H 100-150/5.5-8.0 shows the information of C-H correlation from aromatic. The main structures in lignin were shown in Figure 5 , and the details of assignment were shown in Table 3 ( Ralph et al, 1994 , 1999 , 2004 ; del Río et al, 2008 , 2011 , 2012 ; Kim et al, 2008 ; Martínez et al, 2008 ; Rencoret et al, 2008 , 2009 ; Ralph and Landucci, 2010 ; Ma et al, 2021 ). The strong signals in aliphatic area were generated by β-O-4 linkage in substructures of (A) including A β (G), A β (H), A β (S), and A β (T).…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra of MCSL, WMCSL, and DMCSL were shown in Figure 3, and the assignment of main absorption peaks was depicted in Supplementary Table 7 (Mansouri et al, 2011;Karmanov and Derkacheva, 2013;Joffres et al, 2014;Watkins et al, 2015). The strong absorption in all three samples around 3,400 cm −1 was caused by hydroxyl in carboxylic, phenolic, and alcoholic (Ralph et al, 1994(Ralph et al, , 1999(Ralph et al, , 2004del Río et al, 2008del Río et al, , 2011del Río et al, , 2012Kim et al, 2008;Martínez et al, 2008;Rencoret et al, 2008Rencoret et al, , 2009Ralph and Landucci, 2010;Ma et al, 2021). (Martínez et al, 2008;Wen et al, 2010Wen et al, , 2013.…”
Section: D1-p Can Still Degrade Lignin Through Cleavage Of β-O-4 Linkagementioning
confidence: 98%
“…The abundance of other eight function of the gut microbiota of the 1st instar larvae was higher than that of newly hatched and 4th instar larvae, with one related to ligninolysis. Microbial ligninolysis involves carbon cycling of microorganisms and their enzymes in degradation of lignin, a highly recalcitrant biopolymer embedded between cellulose and hemicellulose structures (Chaudhary & Verma, 2020; Hammel et al, 1993; J. S. Ma, Li, et al, 2021; Vicuña, 2000). It has been found that Raoultella could degrade lignin isolated from Microtermes pakistanicus (F. Li, 2019), cellulose isolated from Batocera lineaolata , Cyrtotrachelus buqueti (H. Tang et al, 2021; Z. D. Yang et al, 2021), and is involved in the synthesis of amino acids and vitamins in Hepialus xiaojinensis (W. Li, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the ability to simultaneously secrete many peroxidase isozymes is a distinctive feature of T. hirsuta species. Similarly with T. hirsuta 072, the T. hirsuta strain X-13 cultivated on lignin-containing media was reported to secrete up to six peroxidase isozymes [57], while the related fungi from Trametes and Pycnoporus genera were reported to secret only from one to four peroxidase isozymes even in wood-containing media [34,54,55,58,59]. The only one reported exception from the above is T. versicolor strain A1-ATF, which secreted from five to nine peroxidase isozymes when cultivated on aspen wafers [56,60].…”
Section: Exoproteomic Studymentioning
confidence: 96%
“…As mentioned above, MnP5 is one of the most abundant peroxidase isozymes in exoproteoms of T. hirsuta 072 regardless of cultivation conditions; however, this is not the case of other Trametes and Pycnoporus spp. Notably, the exoproteome of another T. hirsuta strain X-13 did not contain MnP5 isozyme at all [57]. The only exoproteome in which MnP5 orthologue was found was the exoproteome of T. versicolor cultivated on media containing syringic acid [34].…”
Section: Exoproteomic Studymentioning
confidence: 96%